Nanostructured TiO2-based composites for light absorption - Santos, Dayse L. dos; Modesto Junior, Olayr; Scalvi, Luis Vicente de Andrade [UNESP]; Tabata, Americo S. (Trans Tech Publications, 2014)
Metal oxide nanocomposites were prepared by two different routes: polyol and sol-gel. Characterization by X ray diffraction showed that the first process produces directly a two-phase material, while the sol-gel powder never showed second phase below 600°C. Light spectroscopy of the treated powders indicated similarities for the processed materials. Although the overall material compositions are about the same, different structural characteristics are found for each processing. With the exception of Ti-Zn materials, all the double metal oxide powders showed higher absorbance than either TiO2 powder.